COLREGs-based Situation Awareness for Marine Vessels - a Discrete Event Systems Approach. Issue 2 (2020) - Hansen, P.N.; Papageorgiou, D.; Blanke, M.; Galeazzi, R.; Lützen, M.; Mogensen, J.; Bennedsen, M.; Hansen, D.
Abstract: Autonomy at different levels is envisaged to provide decision support, to enable navigation with temporally unattended bridge or have the navigator placed remotely, being able to take command if required. For this purpose, methods for computer-based situation awareness are needed to avoid risks of collision. Correct interpretation of a situation is crucial, and all navigation decisions must be based on the COLREGs. This paper presents a discrete-event-systems-based framework that facilitates autonomous interpretation of the situation in which the own ship is. This can be used for COLREGs-compliant decision planning when all vessels navigate according to the rules. The proposed framework comprises a set of coupled finite-state deterministic automata and segregates situation understanding from anticipation. The suggested formalism is analysed with respect to avoidance of deadlocks and shows how synchronisation of vessel-specific automata modules is achieved. Simulations illustrate the concept using realistic scenarios.